Low-cost 3D Scanning Table for Educational Purposes - Kohut, Miroslav; Sojka, Adam; Tolgyessy, Michal (2020 23rd International Symposium on Measurement and Control in Robotics (ISMCR), 2020)
Students studying Robotics and Cybernetics have to obtain multiple skills in areas of programming, hardware, 3D vision, etc. Many universities provide different types of hardware for the students to let them gain practical, not just theoretical experience. Universities have difficulties to cover the whole spectrum of knowledge during exercises with a specific type of hardware and teaching becomes more and more expensive. This paper describes a low-cost 3D scanning device that was created to cover the field of robotics and 3D vision, and it can be easily used for educational purposes. The cost of the device is up to 150 Euro and could be used in multiple ways such as microcontroller programming, servo control, 3D vision, 3D modelling and better understanding of space transformation. The device has open API and is fully compatible with ROS (Robot Operating System). In this paper, the function of the device and its integration to the specific subject of study is described. To ensure easier integration to the course, the API description and an open-source package will be provided. In the last part of the paper, it is described how to use the device to help students to understand space and point cloud transformation, basic data filtering and math which is required for obtaining the digital 3D object representation.